Higher-order coping strategies: Who uses them and what outcomes are linked to them. (1st March 2020) - Jonason, Peter K.; Talbot, Daniel; Cunningham, Mitchell L.; Chonody, Jill
Highlights: Secondary principle components analyses run on two, related measures of coping. Three factors emerged; constructive, destructive, and social coping. Sex differences in coping were mediated by personality traits. Destructive coping was linked to more future discounting. Social coping was linked to extraversion, narcissism, and interpersonal trust. Abstract: Many roads to psychological health exist, yet most are likely to conform to systematic, higher-order patterns. In a representative (on age and sex) sample of Australians ( N = 1, 232) and a Mechanical Turk sample from the USA ( N = 602), secondary principle components analyses were conducted on two related measures of lower-order coping strategies (e.g., denial, active planning) revealing three similar (but not identical), higher-order coping strategies, which we called constructive, destructive, and social. Individual differences in these higher-order coping strategies were assessed in relation to personality (e.g., the Big Five, the Dark Triad) and outcomes (i.e., resilience, hopelessness, interpersonal trust, alcohol intake, general health, life satisfaction, and future discounting) in the full sample and in men and women. We found that constructive and destructive coping were rather opposite forms of coping as seen in the nomological network associated with them and modest, negative correlations between them. In contrast, social coping stood slightly on its own vis-à-vis correlations with extraversion, narcissism, and interpersonal trust. We also found sex differences in the higher-order coping strategies which were often mediated by individual differences in personality. Results are discussed in terms of learning, biological, clinical, and evolutionary models of personality and sex differences.